Technology transfer and firm competitiveness: The case of Indonesia - Shujiro Urata; Youngmin Baek (Asian Development Bank Institute (ADBI), 2023)
This paper examines the foreign direct investment (FDI) spillover effects from foreign to domestic firms in Indonesia and assesses the significance of geographical factors on FDI spillover. It uses firm-level data from the Indonesian Bureau of Public Statistics (BPS) covering the period from 2000 to 2009 and focuses on 16 manufacturing sectors. We find an absence of FDI spillover at the country level; however, we observe significant province-level forward FDI spillovers. These findings appear to indicate that intermediate goods supplied by foreign firms raise the productivity of domestic firms via learning, variety, and a quality effect. Our analysis reflects the importance of geographical proximity in realizing forward FDI spillovers. These findings show the importance of developing and improving transportation and telecommunication infrastructure to facilitate FDI spillovers by virtually reducing geographical distance between foreign and domestic firms.
Keywords: D22; F21; O3; 330; foreign direct investment; technology transfer; firm productivity